The occurrence of food hypersensitivity reactions and the relation to the sensitization to grass and trees in atopic dermatitis patients 14 years of age and older - Jarmila Celakovská; Josef Bukac; Karel Ettler; Jaroslava Vaneckova; Irena Krcmova; Kvetuse Ettlerova; Jan Krejsek (Wolters Kluwer Medknow Publications, 2019)
Background: Although epidemiologic data are scarce, there is no doubt that the increase in pollen allergies is going to be followed by an increase in the so-called pollen-related food allergies. The aim of this study was the evaluation of the food hypersensitivity reactions in atopic dermatitis patients and the relation to the sensitization to grass and trees. Methods: The complete dermatological and allergological examinations were performed in all included patients; the occurrence of food hypersensitivity reactions was recorded and the sensitization to inhalant allergens (grass and trees) was examined (skin prick test, and specific IgE). The statistical evaluation of the relation between the sensitization to these inhalant allergens and the occurrence of food hypersensitivity reactions was performed. Results: A total of 321 patients were included, with an average age of 26.7 years (±9.2 years) and with an average SCORAD of 33.2 (±13.3) points. The significant relation was recorded between the patients suffering from sensitization to grass and the reactions to peanuts, celery and walnuts; another significant relation was demonstrated between the patients suffering from sensitization to trees and reactions to apple, peanuts, and walnuts. In patients suffering from sensitization to grass and trees, the occurrence of food hypersensitivity reactions to tomatoes, kiwi, spices, oranges, capsicum, tangerines, and carrot was higher also, but the relation was not significant. Conclusion: The significant relation was found between the reactions to peanuts and walnuts and sensitization to grass and trees, another significant relation was found between the sensitization to grass and celery and between the sensitization to trees and apple.